Magnetic and transport properties of polycrystalline La0.7Sr0.3Mn1-xFexO3. - Araújo, José Humberto de (2020)
The effect of Fe doping (<10%) on polycrystalline samples of La0.7Sr0.3MnO3 has been studied by means of x-ray diffraction, resistivity, ac susceptibility, magnetization, and magnetoresistance measurements. Fe doping does not affect the lattice structure, but it weakens the ferromagnetism and substantially augments the resistivity of the samples. The magnetoresistance of a sample with 10% Fe doping, in a 5 T magnetic field, was 4 times greater than that of the undoped sample near the peak in the resistivity. The results were explained in terms of the formation of antiferromagnetic clusters of Fe ions. At 5 K the magnetoresistance showed no significant dependence on Fe doping, but it displayed large variations in fields below 0.5 T for all samples. This behavior was attributed to spin-polarized tunneling at the grain boundaries of the polycrystalline samples. A variable-range hopping behavior in the resistivity was also encountered in all the samples at low temperatures.